(Invited) Design of Hydrogel Material and 3D-Printed Molding for Imitating the Tactile Textured Properties of Moon Jellyfish. (8th September 2020) - Ogawa, Jun; Yamada, Naoya; Watanabe, Yosuke; Khosla, Ajit; Kawakami, Masaru; Furukawa, Hidemitsu
Abstract : To artificially reproduce the true swimming of a real jellyfish, it is important to find a material that highly approximates the constituent material of the jellyfish and propose a method for shaping it into a three-dimensional model. The body composition of moon jellyfish is gelatinous with a water content of 95% or more, and it has a specific gravity capable of floating in a fluid with a slight flow. This study develops a translucent white hydrogel with this property, and we propose a method for three-dimensional molding of this material as an artificial jellyfish. This paper compares the texture and behavior of artificial jellyfish caused by differences in hydrogel materials and discusses the differences among these features. In addition, we introduce an approach to verify the swimming of hydrogel jellyfish using position-based dynamics-based soft body simulation in virtual space and controllable magnetic stirrer.